Blood flukes Cardicola parvus and C. laruei (Trematoda: Aporocotylidae): life cycles and cryptic infection in spotted seatrout, Cynoscion nebulosus (Teleost: Sciaenidae). Issue 2 (April 2018) - Siegel, Sasha V.; Rivero, Andrea V.; Oberstaller, Jenna; Colon, Beatrice L.; de Buron, Isaure; Kyle, Dennis E.
Abstract: Aporocotylidae comprises a diverse family of fish blood flukes, with adults found in blood or body cavity of marine, brackish, or freshwater fish. Aporocotylids are unique among the Digenea with many developing in polychaetes. The life cycle has been elucidated for only a few species that develop in polychaetes from marine/brackish environments and none for western Atlantic aporocotylids. The basis for this study was observations of blood fluke larvae in annelids from South Carolina, USA in 1982 prior to possible usage of molecular tools to specifically identify parasite larvae. Recent description of aporocotylid species and genotyping tools prompted revisiting original collection sites to examine polychaetes and fish as potential hosts. Polycirrid Enoplobranchus sanguineus and terebellids Amphitrite ornata, and Terebella lapidaria revealed infections with aporocotylid larvae. Adult blood flukes were also collected from fish commonly encountered in the same habitat: spotted seatrout ( Cynoscion nebulosus ), red drum ( Sciaenops ocellatus ), black drum ( Pogonias cromis ), and Atlantic croaker ( Micropogonias undulatus ). Sporocysts containing cercariae were found in individuals of each annelid species. Adult Cardicola parvus were found in spotted seatrout and Atlantic croaker, C. laruei in spotted seatrout, C. currani in red drum, and C. palmeri in black drum. Genotype analysis of ITS-2 and lsrDNA of all forms confirmed conspecific infections by C. parvus in E. sanguineus and A. ornata and C. laruei in T. lapidaria . This is the first description of complete life cycles of aporocotylids in the Western Atlantic and first evidence of cryptic infections of Cy. nebulosus with C. parvus .